Mass Spectrometry Imaging Reveals Spatial Metabolic Alterations and Salidroside’s Effects in Diabetic Encephalopathy - Shuohan Cheng; Xianyue Meng; Zixuan Wang; Tianfang Lan; Zhi Zhou; Zhonghua Wang; Zeper Abliz (Metabolites)
Background: Diabetic encephalopathy (DE) is a neurological complication of diabetes marked by cognitive decline and complex metabolic disturbances. Salidroside (SAL), a natural compound with antioxidant and neuroprotective properties, has shown promise in alleviating diabetic complications. Exploring the spatial metabolic reprogramming in DE and elucidating SAL’s metabolic effects are critical for deepening our understanding of its pathogenesis and developing effective therapeutic strategies. Methods: Air-flow-assisted desorption electrospray ionization–mass spectrometry imaging (AFADESI-MSI) was employed to investigate spatial metabolic alterations in the brains of db/db mice, a spontaneous DE model. The mice were treated with SAL (30 and 150 mg/kg, orally) for 12 weeks. Differential metabolites were identified and characterized using high-resolution mass spectrometry and validated against public databases. Results: Our AFADESI-MSI analysis revealed significant changes in 26 metabolites in the brains of DE mice compared to the controls. These metabolic changes indicated disruptions in glucose, glutamate-glutamine, nucleotide, lipid, choline, aspartate, and L-carnitine metabolism. Notably, glucose 6-phosphate (G6P), glutamine, adenosine, L-carnitine, and choline exhibited similar trends in both db/db mice and STZ-induced rat models of DE, suggesting their potential as reliable biomarkers. Twelve weeks of SAL treatment demonstrated a positive regulatory effect on glucose metabolism, the glutamate–glutamine cycle, and lipid metabolism. Conclusions: This study identifies key metabolic alterations in DE and demonstrates the therapeutic potential of SAL in modulating these disturbances, offering valuable insights for targeted interventions in diabetic complications.